HARNESSING TECHNOLOGY IN EDUCATION: THE EFFECTIVENESS OF WORDWALL GAMES IN ENHANCING STUDENTS' ENGAGEMENT - Hasan, Habil; Imama, Nur; Latif, Fathol; Lambang Rozaqi, Arya Lenza; Hamid, M. Rifqi Abdul; surur, Miftahus (Journal on Research and Review of Educational Innovation, 2024)
Technological developments today have become an essential thing in the learning process. Considering that today's technology exceeds the development of education, input is needed for policy recommendations. In this case, a practical approach to increase students' interest in learning is to use Wordwall educational games. This study aims to determine whether using Wordwall educational games can affect students' learning interests. Based on the research's purpose, the Systematic Literature Review (SLR) method is the right choice. This study collected a literature review of 20 articles from Google Scholar published in the last 5 years from 2020-2024. The analysis results from this collection of articles show that the use of wordwall educational games significantly increases students' interest in learning.